Property Crime in Java Island 2022 based on Demography and Socioeconomic Aspects using Spatial Analysis Approach - Fabian La Wima Vallessy; Timbang Sirait (Limits: Journal of Mathematics and Its Applications, 2025)
Property crime is the most common type of crime in Indonesia with the most rapid increasing in 2022. Java is the island with the highest magnitude of 65.85% if it is compared to the previous year and accounts for more than one third of the total cases in Indonesia. This study aims to determine an overview of these types of criminal offenses and the variables that affect them spatially. The analysis method uses in this study is descriptive analysis which will followed by inferential analysis, namely spatial analysis using Geographically Weighted Negative Binomial Regression (GWNBR). Based on this research, it is found that there are four regional groupings with variables that significantly affect all regions, namely life expectancy and Gini ratio. Meanwhile, there are variables that affect some regions, namely mean years schooling and total population. In addition, it is found that Geographically Weighted Negative Binomial Regression is better used than negative binomial regression in modeling property crime in Java Island in 2022.